The pentose phosphate pathway controls oxidative protein folding and prevents ferroptosis in chondrocytes - Loopmans, Shauni; Rohlenova, Katerina; van Brussel, Thomas; Stockmans, Ingrid; Moermans, Karen; Peredo, Nicolas; Carmeliet, Peter; Lambrechts, Diether; Stegen, Steve; Carmeliet, Geert (Nature metabolism, 2025)
Bone lengthening and fracture repair depend on the anabolic properties of chondrocytes that function in an avascular milieu. The limited supply of oxygen and nutrients calls into question how biosynthesis and redox homeostasis are guaranteed. Here we show that glucose metabolism by the pentose phosphate pathway (PPP) is essential for endochondral ossification. Loss of glucose-6-phosphate dehydrogenase in chondrocytes does not affect cell proliferation because reversal of the non-oxidative PPP produces ribose-5-phosphate. However, the decreased NADPH production reduces glutathione recycling, resulting in decreased protection against the reactive oxygen species (ROS) produced during oxidative protein folding. The disturbed proteostasis activates the unfolded protein response and protein degradation. Moreover, the oxidative stress induces ferroptosis, which, together with altered matrix properties, results in a chondrodysplasia phenotype. Collectively, these data show that in hypoxia, the PPP is crucial to produce reducing power that confines ROS generated by oxidative protein folding and thereby controls proteostasis and prevents ferroptosis.
Keywords: Oxidative Stress; reaktivní formy kyslíku; oxidační stres; pentózofosfátový cyklus; oxidace-redukce; zvířata; myši; glukosa; Reactive Oxygen Species; Glucosephosphate Dehydrogenase; chondrocyty; Mice; Protein Folding; glukosa-6-fosfátdehydrogenasa; sbalování proteinů; Glucose; Pentose Phosphate Pathway; signální dráha UPR; Ferroptosis; ferroptóza; Oxidation-Reduction; Animals; Chondrocytes; Unfolded Protein Response